KUALITAS ORGANOLEPTIK SUSU NABATI BIJI CEMPEDAK (Artocarpus Champeden) TERSUSPENSI PROBIOTIK BERDASARKAN SUHU PENYIMPANAN - Septiana, Nurul; Rohmadi, Mukhlis (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Cempedak (Artocarpus champeden) is a local fruit of Central Kalimantan that is oval with dark yellow and fibrous flesh and has a fragrant aroma when ripe. So far, cempedak seeds have only become organic waste, not used properly. The nutritional and mineral content of cempedak seeds can be used and processed into a healthy drink, namely vegetable milk. Methods: The method used is an experimental method to produce vegetable milk with cempedak seeds which is then carried out organoleptic tests to determine the quality of the aroma and taste of the vegetable milk made. Results: Based on the research carried out, the results showed that the taste quality of vegetable milk of cempedak seeds (Artocarpus champeden) that was most liked by the respondents/panelists was at the temperature of T1=20o C and T2=30o C, which was with a refreshing sweet and sour taste, while for the sour aroma and distinctive smell of cempedak seeds at the temperature of T3=30o C. Conclusion: Cempedak seeds can be used as probiotic plant-based milk with an optimal storage temperature of 30o C to get the distinctive taste, aroma and smell of cempedak seeds.